Attack the Anycast Signature Scheme - Jinbin Zheng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Today, the internet is increasingly being considered to provide services, and not just in order to connect. As this view became more universal, the important factors of providing such services are reliability and availability of the services to meet the needs of a large number of users. Anycast is a communication mode in which the same address is assigned to a group of servers and the router will send the request to the ”best” server. Al-Ibrahim and Cerny proposed an authentication scheme of anycast communication. Their scheme is based on El-Gamal type signature scheme. We prove that their preferred scheme, which does not require interaction among the various signers, is insecure. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4931